Penerapan Metode AHP dan MFEP dalam Pemilihan Asupan Terbaik Anak untuk Pencegahan Stunting - Wardani, Anggika; Samsudin, Samsudin (Program Studi Teknik Informatika Universitas Pamulang, 2023)
Stunting is a condition where children fail or grow late due to malnutrition before and after birth. There are still cases of stunted children in Medan City, one of which is due to public ignorance about the intake that children should consume and not knowing the nutrients contained in the intake, so that people have difficulty choosing intake. Because intake for children is also very important in preventing stunting. Using a decision support system (SPK), recommendations for the best intake for children to prevent stunting can be made. The determination of the best intake criteria for children to prevent stunting is G1 = Formation of body tissue cells, G2 = Increases red blood cells, G3 = Improves brain function, G4 = Helps the growth of bones and teeth, G5 = Supports endurance. By utilizing the Analytical Hierarchy Process (AHP) method to select consistent values to obtain a strong value ratio and strengthen the assessment and also the Multi Factor Evalution Process (MFEP) method which determines the final value to be selected in decision making. By utilizing the AHP and MFEP methods in the decision support system, the results of the study can help the Medan City Health Office to determine the best intake of children to prevent stunting so that it is easier to inform young mothers, pregnant women, and also the people of Medan City.